Marian Revivalism in Modern English Christianity: the Example of Walsingham - Gill, Sean (Studies in church history, 2004)
On 19 August 1897, a newly carved image of Our Lady of Walsingham, sent from Rome by Pope Leo XIII, was solemnly installed in the Roman Catholic Church in Kings Lynn. Since no plan of the original medieval shrine survived, the chapel that contained the image was modelled upon the Holy House of Loreto. The following day a pilgrimage led by the parish priest and by Fr Philip Fletcher, one of the prime movers behind the Marian revival, went from Lynn to the Slipper Chapel at Walsingham. This was an important focus of worship since it was the only building to have survived substantially intact near the great pilgrimage site destroyed at the Reformation. In 1934 the Archbishop of Westminster, Cardinal Bourne, led the first annual Roman Catholic pilgrimage to the Slipper Chapel, in which a new image of Our Lady of Walsingham based upon that of the seal of the medieval Priory had been placed. In the intervening years, the Anglo-Catholic vicar of Little Walsingham, the Revd Arthur Hope Patten, had created a similar shrine in the Anglican parish church in 1922, and had gone on in 1931 to build a separate chapel with its own sanctuary of the Holy House of Nazareth.